Structure, culture and agency : selected papers of Margaret Archer - Archer, Margaret S. (Margaret Scotford); Brock, Tom (New York : Routledge, 2017)
Professor Margaret Archer is a leading critical realist and major contemporary social theorist. This edited collection seeks to celebrate the scope and accomplishments of her work, distilling her theoretical and empirical contributions into four sections which capture the essence and trajectory of her research over almost four decades. Long fascinated with the problem of structure and agency, Archer's work has constituted a decade-long engagement with this perennial issue of social thought. However, in spite of the deep interconnections that unify her body of work, it is rarely treated as a coherent whole. This is doubtless in part due to the unforgiving rigour of her arguments and prose, but also a byproduct of sociology's ongoing compartmentalisation. This edited collection seeks to address this relative neglect by collating a selection of papers, spanning Archer's career, which collectively elucidate both the development of her thought and the value that can be found in it as a systematic whole. This book illustrates the empirical origins of her social ontology in her early work on the sociology of education, as well as foregrounding the diverse range of influences that have conditioned her intellectual trajectory: the systems theory of Walter Buckley, the neo-Weberian analysis of Lockwood, the critical realist philosophy of Roy Bhaskar and, more recently, her engagement with American pragmatism and the Italian school of relational sociology. What emerges is a series of important contributions to our understanding of the relationship between structure, culture and agency. Acting to introduce and guide readers through these contributions, this book carries the potential to inform exciting and innovative sociological research. --
Foreword -- Acknowledgements -- Introduction -- Realism's explanatory framework -- Thinking and theorizing about educational systems -- On predicting the behaviour of the educational system -- The myth of cultural integration -- The vexatious fact of society -- Morphogenesis versus structuration -- For structure : its reality, properties and powers -- The private life of the social agent -- The ontological status of subjectivity -- Reflexivity as the unacknowledged condition of social life -- A brief history of how reflexivity becomes imperative -- Self-government & self-organization as misleading metaphors -- The generative mechanism re-configuring late modernity -- How agency is transformed in the course of social transform -- Trajectory of the morphogenetic approach -- Interview with Maggie -- Annotated bibliography -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Social structure; Realism; Culture; Organization; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Essays